Effect of algae fuel addition on fuel consumption and thermal efficiency of single cylinder diesel engine. Issue 1 (March 2021) - Sharudin, Hazim; Rahim, N.A.; Ismail, N.I.; Mat, Sharzali Che; Abdullah, Nik Rosli; Zulkifli, N.W.M.; Yusoff, M.N.A.M.
Abstract: The objective of this paper is to evaluate the brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) of algae fuel blended in diesel fuel. Fuel blends of 1% of algae fuel (B1), 2% of algae fuel (B2), 3% of algae fuel (B3) and 4% of algae fuel (B4) to each 100 ml of fuel blend volume were prepared. Each algae-diesel fuel blend was tested on single-cylinder diesel engine by varying the engine loads (0, 2, 4 and 6 Nm) at a constant engine speed of 1500 rpm. Different BTE and BSFC engine performance levels were the measured parameters. Based on the result of the engine performance tests, it can be concluded that B4 blends in diesel fuel produced better BTE with 17% at 4 Nm engine load than diesel fuel. Meanwhile, the BSFC was lower for B4 with 16% compared to diesel fuel at lower engine load.